Synthesis and characterization of mesoporous MOF UMCM-1 for CO2/CH4 adsorption; an experimental, isotherm modeling and thermodynamic study - Ullah, S. (Elsevier B.V., 2020)
In this work, a metal-centered organic framework (UMCM-1) demonstrating microporous nature was prepared by the combination of the organic linker 1,3,5-tris(4-carboxyphenyl) benzene (H2BTB) and the salt Zinc Nitrate Hexahydrate (Zn-(NO3)2Â·6H2O) via solution-based, catalyst-free, and direct mixing method. The structural characteristics and porous properties of UMCM-1 were investigated by surface morphology, functional groups analysis, crystallinity, thermal stability, texture characteristics via FESEM, FTIR, PXRD, thermal stability analysis, porous properties, respectively, and pure gases (CO2 and CH4) uptake behaviour. The pure CO2 and CH4 adsorption were acquired out at a pressure of 1 bar and at three various temperatures i.e. 298.15 K, 323.15 K, and 348.15 K. The N2 adsorption-desorption isotherms reveal their highly microporous nature with specific surface area (3481.0667 m2/g), pore size (19.9373 Ã ), and the pore volume (0.0178 cm3/g). The UMCM-1 was found crystalline and highly stable under harsh thermal conditions. The CO2 uptake capacity (1.0732 mmol/g) was found to be 138.48 approximately higher than CH4 uptake capacity (0.45 mmol/g). By increasing temperature, 10.7 approximately loss in the uptake capacities of CO2 and CH4 was observe demonstrating the exoergic in nature i.e. energy-releasing adsorption phenomenon. Furthermore, the isotherms and thermodynamic study demonstrated that the adsorption phenomenon is favorable adsorption behaviour with the heterogeneous system, demands higher pressure adsorption to activate the pores and physical in nature. The results presented herein demonstrated the UMCM-1 as a promising candidate for the energy-efficient CO2 separation. Â© 2019 Elsevier Inc.